Techniques employed by Reprographic and Digitization Unit over a span of 65 years of its activity - Katarzyński, Jerzy (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article describes the transformations in preservation techniques and access to library resources which have taken place in Reprographic and Digitization Unit, Wrocław University Library, over a span of 65 years of its functioning. It discusses how the analog-digital breakthrough in the sphere of data carriers and methods of their recording challenged the Unit into searching for qualitative balance between traditional methods of preserving and access to collections and their electronic counterparts. Presented are also the processes of collections digitization, including Europeana, to Digital Library of University of Wrocław and to various projects which aim to collection preservation and at the same time allow for open, unlimited by time and space, access to their digital copies.
Keywords: microfilming; electrography; preservation; Reprographic and Digitization Unit; reprography; photography; digital recording; copying; Wrocław University Library; scanning; digitization